NORMATIVE POWERS OF SERBIAN LOCAL AUTHORITIES - Jerinić, Jelena; Milosavljević, Bogoljub (Pravni zapisi, 2019)
Authors analyse Serbian legislation in respect of regulatory autonomy of local governments, i.e. the authorisation of different local government bodies to pass ordinance and bylaws in realisation of local competences. The analysis is based on the provisions of the Serbian constitution and relevant legislation, as well as substantial law of the Serbian Constitutional Court, as well as interpretation of relevant principles of the European Charter of Local Self-Government. They conclude that local assemblies, as local representative bodies, are the only ones generally empowered to pass bylaws in the areas of own competence of local governments and that other bodies, namely the local executive council can do so only in existence explicit delegation in law – either the Law on Local Self-Government or other law. The authors have found only two such examples, while the case law of the Constitution show ample proof of bylaws passed by the local executive and administration without specific authorisation in the law. The most common are cases in which local assemblies entrusted other local government bodies in passing bylaws in issues in local competence, as well as cases in which executive bodies or the local administration attempted to fill in the gaps in the existing local regulations, by passing general acts, when the matter should have been regulated by the local assembly.In that view, the authors recommend even further clarification of the current norms of the Law on Local Self-Government and, in the future, possibly the Constitution.